HASIL TANGKAPAN DAN KONDISI HABITAT IKAN TOR (Tor spp.) DI HULU DAS WAMPU KABUPATEN LANGKAT SUMATERA UTARA - Jeni Ariyanti; Desrita Desrita (Program Studi Manajemen Sumberdaya Perairan, Fakultas Pertanian Universitas Sumatera Utara, 2018)
The aim of this research is to know the catch of Tor fish (Tor spp.) and Tor trower habitat condition (Tor spp.) in Upstream Wampu Basin of Langkat Regency of North Sumatera. Sampling was conducted for three months, from July to September 2017. Fish was caught with backpack electrofishing units. Water quality measurement was done in situ. The catch in the Berkail River was higher than the catch in the Bahorok River, because the Berkail River has more dense vegetation than the Bahorok River. Overall, the water condition in Upper DAS Wampu is still above the standard quality water quality threshold.Keywords: Catch, Water Condition, Tor Fish (Tor spp.)